2014
DOI: 10.2147/nds.s57602
|View full text |Cite
|
Sign up to set email alerts
|

A 2-month exposure to dietary genistein has sex-dependent effects on serum profile, cardiac protein expression, and aortic morphology in mice

Abstract: Background:The sex-dependent effects of chronic exposure to dietary genistein on cardiovascular health are poorly understood. Purpose: This study examined the effects of a genistein-containing diet on cardiovascular plasma markers, aortic morphology, blood pressure, and expression of cardioprotective proteins in male and female mice. Methods: C57BL/6J mice were fed either genistein diet (600 mg genistein/kg diet; 600G) or a genistein free diet (0G) for a period of 2 months. Results: After treatment, male and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…We first determined total GLUT4 content in hearts from mice fed genistein for a period of 4 weeks. As shown in Figure 3 , feeding mice a genistein-containing diet increased the expression of total GLUT4, confirming our earlier findings [ 17 ]. Western blot analysis revealed that cardiac GLUT4 expression was significantly increased in both male (1.51-fold from 0.79 ± 0.25 ( n = 10) to 1.18 ± 0.51 ( n = 9), P < 0.05) and female (1.76-fold from 0.52 ± 0.13 ( n = 10) to 0.92 ± 0.29 ( n = 10), P < 0.05) mice fed 600 G. Interestingly, male control mice (0 GM) had significantly greater GLUT4 expression (1.52-fold) compared to females control counterparts.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We first determined total GLUT4 content in hearts from mice fed genistein for a period of 4 weeks. As shown in Figure 3 , feeding mice a genistein-containing diet increased the expression of total GLUT4, confirming our earlier findings [ 17 ]. Western blot analysis revealed that cardiac GLUT4 expression was significantly increased in both male (1.51-fold from 0.79 ± 0.25 ( n = 10) to 1.18 ± 0.51 ( n = 9), P < 0.05) and female (1.76-fold from 0.52 ± 0.13 ( n = 10) to 0.92 ± 0.29 ( n = 10), P < 0.05) mice fed 600 G. Interestingly, male control mice (0 GM) had significantly greater GLUT4 expression (1.52-fold) compared to females control counterparts.…”
Section: Resultssupporting
confidence: 91%
“…However, in addition to these differences in plasma insulin and glucose to genistein treatment, which makes it difficult to accurately assess how genistein affects glucose metabolism, we have previously demonstrated that this phytoestrogen administered for a period of 2 months increases the expression of the glucose transporter GLUT4 in male murine cardiac tissue [ 17 ]. We further confirm this finding in this current study with the significant increase in the expression of total protein GLUT4 content following genistein treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genistein-containing diet (Gen) was purchase from Dyets Inc. (Bethlehem, PA) and contained 600 mg genistein/kg diet. The composition of the genistein diet has been published previously [ 9 , 13 , 14 ]. Food and water were provided ad libitum.…”
Section: Methodsmentioning
confidence: 99%